Women on social media: A representation of self-actualization and social embarrassment - Irawati, Irawati; Hasgimianti, Hasgimianti; Raja, Rahima; Fitra, Herlinda (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
This article aims to explore how women utilize social media, their objectives for its use, and the content they typically engage with. Social media serves as a platform for individuals of all genders to self-actualize. However, it is noteworthy that there are minimal restrictions on women's access to social media, allowing them to explore various content at any time, potentially leading to legal issues today. This adverse impact has been evidenced in several cases and extensively discussed in numerous studies. Additionally, women's experiences of embarrassment on social media have been emphasized in their pursuit of self-actualization online. This study employs a quantitative approach utilizing a survey method to analyze the trends, attitudes, and opinions of a population through a sample examination. The study focused on a small group aged between 17 and 40, identified as active users of social media. The research sample comprised 182 individuals and was conducted between March and July 2022 in Pekanbaru. The research findings reveal that 35.7% of women utilize social media primarily to share their best photos as a form of self-actualization, while 41.2% access marketplace and engage in online shopping as their most frequent activities. Furthermore, women's self-actualization as social media users was assessed as medium, with a percentage of 35%, and their experiences of social embarrassment on social media were classified as medium as well, with a percentage of 42%.